Risk Factors for Obstetric Emergencies With Referral Implementation at the Palembang Health Center - Tafdhila Tafdhila; Dessy Suswitha; Dewi Rury Arindari (Jurnal Ilmu Kedokteran dan Kesehatan, 2023)
Obstetric emergencies are potentially life-threatening conditions that can occur in pregnant women and even during delivery. The main causes of obstetric emergencies (APGO, AGO and AGDO) are due to bleeding during childbirth, septic infection, hypertension, preeclampsia or eclampsia, and dystocia. One of the effective management efforts in obstetric emergencies is the implementation of appropriate and planned referrals that can save mothers and newborns. The purpose of this study was to determine the risk factors for obstetric emergencies with referrals at the Palembang Health Center. Methods: Quantitative research using a cross sectional approach. The population is all pregnant women who carry out examinations at the Palembang Health Center with a total sample of 128 pregnant women. The results showed that the highest frequency of cases in the APGO risk factor group was pregnant women aged ≥ 35 years (35.9%), in the AGO group it was serotonin (43%), in the AGDO group it was severe preeclampsia/eclampsia (13.3%) , the highest scoring group was High Risk Pregnancy (KRT) (11.7%) and the most referral criteria were planned referrals (91.4%). In conclusion, there was no significant difference in the risk factors for obstetric emergencies in the APGO variable p=0.727 and AGO p=0.328 between planned referrals and late referrals (p>0.05), but there were significant differences in the risk factors for obstetric emergencies in the AGDO variable between planned referrals and referrals late p=0.011 (p<0.05)